MODAL SOSIAL UNTUK PENGEMBANGAN ORGANISASI: STUDI PADA AISYIYAH KOTA BAUBAU - Andy Arya Maulana Wijaya (JSSH (Jurnal Sains Sosial dan Humaniora), 2019)
Gender segregation within the organization is still common, including for Muhammadiyah as a group of men and Aisyiyah as a group of women. This study aims to examine Social Capital Capability of Aisyiyah Baubau, according to the trust of the society to the movement of this organization generally increase with a number of Amal Usaha Muhammadiyah (AUM) in Baubau City. This study categorizes that internal social capital is stronger than the external social capital of the organization’s, it provides a description that Aisyiyah Baubau City is capable of managing members and AUM as a form of organizational development effort, it's just not optimal in building network against stakeholders and local government. In the other hand, aisyiyah baubau in also influenced by social cultural condition of buton society which has a lot of distance ideologically with muhammadiyah.